Real Interest Rates, Anticipated Inflation, and Unanticipated Money: A Multi-Country Study - Dennis L. Hoffman; Schlagenhauf, Don E. (The Review of Economics and Statistics, 1985)
Dennis L. Hoffman and, Don E. Schlagenhauf, Real Interest Rates, Anticipated Inflation, and Unanticipated Money: A Multi-Country Study, The Review of Economics and Statistics, Vol. 67, No. 2 (May, 1985), pp. 284-296